(untitled) (Research, Society and Development, 2020)
The present study aims to describe a pedagogical experience, through activities related to entrepreneurship in education, using technological devices with students of a social project. To carry out this study, the data collected characterized the profile of the students, the activity developed through entrepreneurship in education with the use of technology and the evaluation of the experience lived by the students. The research is justified by the importance of entrepreneurship in education, combined with technologies, encompassing the development of the ability to take calculated risks and the training of creative and innovative students. The study is classified as a qualitative, descriptive, experience report type research. The context in which the research was carried out was a social project, which welcomes students in the opposite direction to their regular classroom activities. In this project, school reinforcement activities, music, dance and entrepreneurial education are developed. To this end, the results indicate that the participation of students in the project led to the construction of a new vision on the use of technologies and fostered the entrepreneurial capacity to face daily challenges in a creative and innovative way.